The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1136/emermed-2019-208665
|View full text |Cite
|
Sign up to set email alerts
|

Massive transfusion in The Netherlands

Abstract: ObjectivesMassive transfusion protocols (MTPs) may improve survival in patients with uncontrolled haemorrhage. An MTP was introduced into the Dutch transfusion guidelines in 2011, the ninth edition of the advanced trauma life support course in 2012 and the third version of the European guideline in 2013. This is the first survey of MTPs in Dutch trauma centres.MethodsThe aim of the study was to compare MTP strategies in level 1 trauma centres in The Netherlands, and with (inter)national guidelines. A contact i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…43,44 Based on the data of this study, WB has equal fibrinogen content as a unit of apheresis plasma despite its higher plasma volume, which is due to the higher citrate dilution of WB compared to apheresis plasma. 45 Furthermore universal donor type O required for early transfusion of WB, has lower factor VIII activities compared to other blood groups. 46 In clinical practice these small differences in coagulation factor activity will probably have minimal impact on the clinical outcome of patients with major hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Based on the data of this study, WB has equal fibrinogen content as a unit of apheresis plasma despite its higher plasma volume, which is due to the higher citrate dilution of WB compared to apheresis plasma. 45 Furthermore universal donor type O required for early transfusion of WB, has lower factor VIII activities compared to other blood groups. 46 In clinical practice these small differences in coagulation factor activity will probably have minimal impact on the clinical outcome of patients with major hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…With approximately 40 0-50 0 admitted severely injured trauma patients (with injury severity score of ≥ 16) and 160 MTP activations, annually this level 1 trauma centre has the highest polytrauma patient load in the Netherlands. [10] A total of 113 surveys were sent to potential local respondents situated in the departments of surgery ( n = 33), anaesthesiology ( n = 50) and the emergency department (ED) ( n = 30).…”
Section: Local Survey: Within All Departments Of One Level 1 Trauma Centrementioning
confidence: 99%
“…[ 8 , 9 ] Despite availability of a national guideline in the Netherlands, MTP content in all level 1 trauma centres is varying and whether transfusion practice is concordant with local MTP or is driven by expert opinion or other guidelines is currently not known. [10] Albeit the evidence that early and correct MTP use results in improved coagulation, survival benefit and cost reduction, it is expected that actual knowledge regarding the correct MTP strategy is low. [ 5 , 11-14 ] The aim is to determine MTP knowledge and massive transfusion strategy for trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…( 8) 18) It should however be noted that even between trauma centres there is a significant variation in practice and the regimen used. (33) Looking at adverse events between groups, one study (n= 354) reported a higher incidence of AKI in the WB group compared with component therapy. (30) Another study (n=369) found a higher incidence of ARDS in the FWB group compared to aPLT group.…”
Section: Sub-analysis Of Patients With Tbimentioning
confidence: 99%